개정된 CAPSS 기반 충남의 대기오염물질 배출량 변화와 지역 대기질 개선을 위한 정책 제언 - 김종범; 황규철; 박세찬; 이가혜; 노수진; 김정호; 이재영; 박종성 (한국대기환경학회지, 2023)
Since 1999, the Ministry of Environment has been utilizing the Clean Air Policy Support System (CAPSS) to assess and establish for air quality management based on the quantification of domestic air pollutant emissions. CAPSS categorizes nine air pollutants released within the area into point, area, and mobile sources, and proceeds to calculate their emissions. This process relies on scientific calculation methods, which take into account factors such as the raw materials utilized in each region, activity data, and emission factors. As a result of the recent modification in the calculation methodology, CAPSS has undergone an upgrade from version 5 to version 6, necessitating a comprehensive comparative analysis. Hence, this research aims to examine the emission characteristics of each city and county within Chungcheongnam-do, a region known for its concentration of major domestic large-scale discharge facilities, in light of both the previous and revised CAPSS. Specifically, Chungcheongnam-do hosts the nation’s largest coal-fired power generation belt, spanning across Dangjin, Taean, Boryeong, and Seocheon in the northwest. Furthermore, the area houses the Seosan (Daesan) Petrochemical Complex, which is acknowledged as one of the nation’s three largest petrochemical complexes. It is located between Dangjin and Taean. To effectively address air quality management, it is crucial to analyze the multifaceted sources of emissions and establish tailored emission reduction policies for each region. However, the current approach of implementing nationwide management measures by dividing the country into four regional zones raises concerns regarding its effectiveness. In the case of Chungcheongnam-do, it is categorized into three types based on emission characteristics: energy industry, urban-rural mixing, and agricultural production types. In order to achieve more impactful improvements in the future, it is imperative to propose customized policies that take into account the specific emission characteristics of each type, thus overcoming the challenges associated with the current management approach.
Keywords: Modified CAPSS; ChungNam; Environmental policy; Air pollutants emission; Region characteristics